Business games as teaching tools: an analysis of its application in the field of marketing management - Antonio Chamorro Mera; Francisco Javier Miranda González; José Manuel García Gallego (Universitat Politècnica de València, 2015)
Technological advances and Web applications have allowed extending the use of simulators or business games at university teaching. This is an active methodology to develop student skills that are included in curricula of administration and business management degrees and masters.In this paper, we describe the use of SIMBRAND simulator as a teaching methodology at Master in Marketing and Market Research at the University of Extremadura. The results were positively assessed by the students and teachers involved in the project. The experience also reveals the need of considering some key aspects for the proper use of this tool, such as the planning and definition of the evaluation system, continuous monitoring and guidance from teacher to students and learning that students should have received previously from both the simulator and the teams' management.